PELAKSANAAN RAPAT UMUM PEMEGANG SAHAM PERUSAHAAN TERBUKA SECARA ELEKTRONIK (E- RUPS) DENGAN SISTEM E-PROXY DI PT. TELEKOMUNIKASI INDONESIA (Persero), Tbk - Khairu, Harsa; Azheri, Busyra; Mannas, Yussy Adelina (Universitas Ekasakti, 2023)
The purpose of this research is to find out the implementation of the electronic General Meeting of Shareholders (e-RUPS) using the e-proxy method at PT Telkom and to find out how the Notary's authority is in holding the General Meeting of Shareholders electronically. The research method that researchers use is Empirical Juridical law (sociolegal research). The data that has been collected will then be analyzed using a qualitative approach, namely research procedures that produce descriptive data. The research results of PT Telkom as one of the users of the easy.KSEI applications have carried out e-RUPS since the Covid-19 pandemic hit Indonesia in 2020 until the last e-RUPS in 2022.